Kedudukan Hukum Pemegang Unit Penyertaan Reksa Dana Kontrak Investasi Kolektif - Nazarudin Nazarudin (Fakultas Hukum Universitas Islam Indonesia, 2004)
The holder unit of reksadana participation become the third party on collective investment contract between investment manager and kustodian bank who is taking their agreement for holder interest participation unit In the construction of private law, the holder interest participation un it have authority to the investment manager and kustodian bank.